Helicobacter pylori Infection of Primary Human Monocytes Boosts Subsequent Immune Responses to LPS - Frauenlob, Tobias; Neuper, Theresa; Mehinagic, Muamera; Dang, Hieu-Hoa; Boraschi, Diana; Horejs-Hoeck, Jutta (Frontiers in Immunology, 2022)
Infection with Helicobacter pylori affects almost half of the world's population and is a major cause of stomach cancer. Although immune cells react strongly to this gastric bacterium, H. pylori is still one of the rare pathogens that can evade elimination by the host and cause chronic inflammation. In the present study, we characterise the inflammatory response of primary human monocytes to repeated H. pylori infections. We show that, although repeated stimulations with H. pylori do not result in an enhanced response, H. pylori-primed monocytes are strongly activated by a subsequent LPS stimulation. Thus, H. pylori infection apparently triggers a kind of "innate memory" response similar to the unique sustained response in invertebrates, aimed at maintaining a fully efficient response in the face of overlapping challenges, but vulnerable to the development of chronic inflammation. Conversely, stimulation with heat-killed bacteria results in a tolerance that aims to develop tissue-sparing defence responses to subsequent challenges. This profile is also observed when the secondary challenge occurs several days after the primary infection with live bacteria, a situation that mimics the resolution of the infection and the return to baseline. The observation that H. pylori makes primary human monocytes more susceptible to subsequent/overlapping stimuli provides an important basis for a better understanding of how H. pylori can maintain chronic inflammation and thus contribute to gastric cancer progression.